International Prevalence and Mechanisms of SARS-CoV-2 in Childhood Arterial Ischemic Stroke During the COVID-19 Pandemic. Issue 8 (5th April 2022) - Beslow, Lauren A.; Agner, Shannon C.; Santoro, Jonathan D.; Ram, Dipak; Wilson, Jenny L.; Harrar, Dana; Appavu, Brian; Fraser, Stuart M.; Rossor, Thomas; Torres, Marcela D.; Kossorotoff, Manoëlle; Zuñiga Zambrano, Yenny C.; et al.
Abstract : Background: Data from the early pandemic revealed that 0.62% of children hospitalized with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) had an acute arterial ischemic stroke (AIS). In a larger cohort from June 2020 to December 2020, we sought to determine whether our initial point estimate was stable as the pandemic continued and to understand radiographic and laboratory data that may clarify mechanisms of pediatric AIS in the setting of SARS-CoV-2. Methods: We surveyed international sites with pediatric stroke expertise to determine numbers of hospitalized SARS-CoV-2 patients <18 years, numbers of incident AIS cases among children (29 days to <18 years), frequency of SARS-CoV-2 testing for children with AIS, and numbers of childhood AIS cases positive for SARS-CoV-2 June 1 to December 31, 2020. Two stroke neurologists with 1 neuroradiologist determined whether SARS-CoV-2 was the main stroke risk factor, contributory, or incidental. Results: Sixty-one centers from 21 countries provided AIS data. Forty-eight centers (78.7%) provided SARS-CoV-2 hospitalization data. SARS-CoV-2 testing was performed in 335/373 acute AIS cases (89.8%) compared with 99/166 (59.6%) in March to May 2020, P <0.0001. Twenty-three of 335 AIS cases tested (6.9%) were positive for SARS-CoV-2 compared with 6/99 tested (6.1%) in March to May 2020, P =0.78. Of the 22 of 23 AIS cases with SARS-CoV-2 in whom we could collect additional data, SARS-CoV-2 was the main stroke risk factor in 6 (3 with arteritis/vasculitis, 3 with focal cerebral arteriopathy), a contributory factor in 13, and incidental in 3. Elevated inflammatory markers were common, occurring in 17 (77.3%). From centers with SARS-CoV-2 hospitalization data, of 7231 pediatric patients hospitalized with SARS-CoV-2, 23 had AIS (0.32%) compared with 6/971 (0.62%) from March to May 2020, P =0.14. Conclusions: The risk of AIS among children hospitalized with SARS-CoV-2 appeared stable compared with our earlier estimate. Among children in whom SARS-CoV-2 was considered the main stroke risk factor, inflammatory arteriopathies were the stroke mechanism.